Consumers’ Impulse Buying Behaviors Vis-à-vis Visual Merchandising in Selected Malls in Pampanga - Yturralde, Chere’ C.; Lazatin, Wilhelmina D. (Future Science / FSH-PH Publications, 2022)
The study was focused on assessing the consumers’ impulse buying behaviors as to the relationship to visual merchandising. According to Foroughi et al. (2013), one of the many tactics that companies do practice includes encouraging customers to buy impulsively. Because of this theory and visual merchandising, the researcher was able to determine consumers’ impulsive buying behavior concerning visual merchandising. In this study, 384 mall shoppers were selected as the population sample from the three selected Malls in Pampanga. The collected data were analyzed through frequency, mean, Likert scale, Pearson correlation, and Chi-square to test respondents’ profile with their impulse buying behavior, respondents’ profile and their assessment of visual merchandising, and respondents’ impulse buying behavior and their assessment of visual merchandising. Consumer impulse buying behavior has a significant relationship with the window display. According to Bhatti and Latif (2013), said that when the consumers visualize the products which were displayed attracts the customers and arouses their urge to do impulse buying. Visual merchandising including window display, in-store display, floor merchandising, and promotional signage make a significant effect on stimulating the consumers’ impulse buying behavior. For future researchers, further studies may be used, like for instance introducing other variable/s in assessing consumers’ buying impulsiveness not only limited to visual merchandising per se but also identifying a specific product.